Viscosity Approximation Methods for Generalized Multi-Valued Nonexpansive Mappings with Applications. (3rd October 2018) - Pant, Rajendra; Shukla, Rahul; Petruşel, Adrian
Abstract: In this article, we study viscosity approximation methods for generalized multi-valued nonexpansive mappings and we present some new results related to strong convergence, variational inequality, convex optimization, split and common split feasibility problems (SFPs). Some numerical computations are also presented to illustrate our results.